Proposta de leitura interacionial do gênero conto a partir de um objeto de aprendizagem - quiz - Santos Filho, José Raimundo dos (2016)
This research proposes the development of reading comprehension of students of the 8th grade of elementary school, enrolled in CEJM in an interactionist reading perspective, through the collaborative construction of a learning object (LO), based on studies of Kleiman (2013) among others. The reading comprehension is conceptualized from Solé studies (1998); the conception of genre is from Bakhtins (1992), but mostly considers the contributions of Marcuschi (2008) and Antunes (2003) regarding the work with texts; the conception of the genre tale is supported by Cortázar (2011) and Gotlib (1999); the discussion of learning object is found in Araújo (2013) the main reference; and the procedures adopted in the action research undertaken follows the concept of Thiollent (2001). The choice of genre tale is justified by the fact that CEJM students, in the municipality of Japoatã – Sergipe, already know it, but present difficulties of understanding as to its organization, the constituent elements, as well as in relation to contextual factors that affect the interpretation of texts. The survey was conducted in three stages, namely: 1st) analysis for the reader profile of students and about the used reading strategies; 2nd) study of the constituents of the genre tale, through a sequence of activities; 3rd) construction of a learning object (quiz), with the collaboration of students. Different instruments were mobilized to achieve this work, questionnaires, methodological and procedural reporting and tabulating data concerning the performance of students after the completion of the activities contained in the quiz of Understanding. After finishing the application of the quiz, it was observed that the average score was twenty questions, considering the 28 that make up the LO, and that no student scored less than 10 questions (35% accuracy), although there are differences in the level of difficulty: 85.33% hit issues level 1, 70% of level 2 and 56.66% of level 3, which may be assessed as an average performance throughout the class. When considered that the school has not surpassed the level 2 of the eight proposed for the assessment of reading comprehension by Prova Brasil, there is a breakthrough in reading comprehension, but above all, it is clear the need for the work to be continued and be intensified gradually.